1999
DOI: 10.1007/bf03162073
|View full text |Cite
|
Sign up to set email alerts
|

Spectrometer for optical detection of magnetic resonance: Magneto-optical study of Yb3+ in BaF2 single crystal

Abstract: A home-built multifunctional computerized spectrometer for optical detection of magnetic resonance (ODMR) is described. Preliminary results of studying Yb 3 + ions in BaF, single crystal by electron paramagnetic resonance, ODMR and optical spectroscopy are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…[8]. EPR experiments were carried out on modified an X-band spectrometer ERS-231 (Germany) [9] at 4.2 K. Optical spectra were recorded at T ¼ 2; 77 and 300 K on a home built multifunctional computerized spectrometer [10]. Luminescence in crystals was excited with a xenon lamp of 1 kW power.…”
Section: Resultsmentioning
confidence: 99%
“…[8]. EPR experiments were carried out on modified an X-band spectrometer ERS-231 (Germany) [9] at 4.2 K. Optical spectra were recorded at T ¼ 2; 77 and 300 K on a home built multifunctional computerized spectrometer [10]. Luminescence in crystals was excited with a xenon lamp of 1 kW power.…”
Section: Resultsmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) experiments were carried out at T ¼ 4.2 K. The analysis of the EPR spectra has shown that Yb 3+ ions form one paramagnetic center of cubic symmetry (T c ) and substitute only for Y 3+ in Cs 2 NaYF 6 [12,13]. Optical spectra were registered on a homebuilt multifunctional spectrometer [14] at T ¼ 2, 77 and 300 K. The luminescence of the crystal was excited by the light of a xenon lamp (power 1 kW). Luminescence excitation spectra were corrected on the spectrum of the lamp radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The optical measurements were car¡ out on CaF 2 crystals with YbF 3 or Yb203 concentrations C of 0.01%, 0.1% and 0.2%. The measurements were carried out on a modified ERS-231 spectrometer (Berlin, Center for Scientific Instrument) [12] at T= 4.2 K. Optical spectra at T = 2, 77 and 300 K were recorded on a homebuilt multifunctional spectrometer [13]. The luminescence of the crystals was excited by the output of a xenon lamp (powš of 1 kW), passing through a red glass filter.…”
Section: Resultsmentioning
confidence: 99%